Third Five-Year Plan Madras State Review Of Progress During 1961-62 To 1964-65 And Programme For 1965=66 - Planning Commission (Planning Commission, 1965)
This publication seeks to set out in detail the progress achieved so far in the Third Plan period under the various schemes as well as the programme for 1965-66. The details of actual expenditure in 1961—62, 1962-63 and 1963-64 and the anticipated expenditure in the current year and the budgeted outlay for 1965-66 are also given in respect of all schemes under each head oi development. The Committee on Agricultural Production constituted to finalise the Third Plan programme examined the seasonal variation between the favourable season and adverse season and indicated that the difference between the two would be of the order of 10 lakh tonnes.
Finance (Planning and Development ) Department Government of madras